Navigating Homelessness Assistance While Pregnant: A Rapid Qualitative Research-to-Policy Collaboration in Washington, DC - Christina X. Marea; C. Anneta Arno; Kelly Sweeney McShane; Andrew Lozano; Makeda Vanderpuije; Kelley N. Robinson; Karen Trister Grace; Noelene Jeffers (Health Equity)
Background: Homelessness during pregnancy contributes to adverse pregnancy and infant outcomes from birth through early childhood. Washington, DC, a microcosm of structural inequities in the United States, has persistent racial disparities in perinatal outcomes and housing insecurity. Methods: Grounded in a reproductive justice framework, we explored the lived experience of navigating homelessness assistance while pregnant to inform recommendations for a collaborative policy and practice change effort. We conducted 20 individual interviews with DC residents who experienced homelessness during pregnancy. We analyzed the data using thematic analysis and an action-oriented approach. Results: Our analysis resulted in three main recommendation areas for policy and practice change: (1) timely and meaningful access to safe and stable housing in pregnancy; (2) care coordination for services and referrals that support physical, mental, and social well-being; and (3) access to a living wage and affordable housing. Discussion: Access to stable housing is critical to ensure that pregnant and parenting people can have and raise children in a safe and sustainable environment—key tenets of reproductive justice. Housing support must be meaningfully accessible, including service delivery that accommodates the complex social histories and competing demands that accompany housing insecurity. Health Equity Implications: This study informed the development of strategic recommendations, catalyzed a new model for multisector collaboration, and influenced a system-wide practice change to expand access to robust housing supports for pregnant people. Policy and practice change require sustained leveraging of political will to promote economic justice and ensure that residents can achieve safe, sustainable, and affordable housing.